Role of land access in youth migration and youth employment decisions: Empirical evidence from rural Nigeria - Ghebru, Hosaena; Amare, Mulubrhan; Mavrotas, George; Ogunniyi, Adebayo (International Food Policy Research Institute, 2018)
The paper examines the role of land access in youth migration and employment decisions using a two wave panel data set from the Living Standards Measurement Study—Integrated Surveys on Agriculture (LSMS-ISA) from Nigeria. Overall, the findings show that the size of expected land inheritance is significantly and negatively associated with long distance migration and migration to urban areas, while a similar impact is negligible when a broader definition of migration is adopted and when migration is deemed as temporary. A more disaggregated analysis by considering individual characteristics of the youth shows that results are more elastic for older youth and those that are less educated, while we find no difference when comparisons are made by gender. Similar analysis on the influence of land access on youth employment choices shows strong evidence that the larger the size of the expected land inheritance the lower the likelihood of the youth being involved in non-agricultural activities and a higher chance of staying in agriculture or the dual sector. The results further reveal that youth in areas with a high level of agricultural commercialization and modernization seem to be more responsive to land access considerations in making migration and employment decisions than are youth residing in less commercialized areas. Finally, the results from the differential analysis suggest that rural-to-urban migration and the likelihood of youth involvement in the dual economy is more responsive to the size of the expected land inheritance for less educated youth as compared to more educated ones.